Viral oncogene-induced DNA damage response is activated in Kaposi sarcoma tumorigenesis. - Sonja Koopal (Public Library of Science (PLoS), 2007)
Kaposi sarcoma is a tumor consisting of Kaposi sarcoma herpesvirus (KSHV)-infected tumor cells that express endothelial cell (EC) markers and viral genes like v-cyclin, vFLIP, and LANA. Despite a strong link between KSHV infection and certain neoplasms, de novo virus infection of human primary cells does not readily lead to cellular transformation. We have studied the consequences of expression of v-cyclin in primary and immortalized human dermal microvascular ECs. We show that v-cyclin, which is a homolog of cellular D-type cyclins, induces replicative stress in ECs, which leads to senescence and activation of the DNA damage response. We find that antiproliferative checkpoints are activated upon KSHV infection of ECs, and in early-stage but not late-stage lesions of clinical Kaposi sarcoma specimens. These are some of the first results suggesting that DNA damage checkpoint response also functions as an anticancer barrier in virally induced cancers.